Recommendations for Sustainable Waste Management Technology in Palembang City - Setiawan, Heri; Susanto, Sani; Budiarto, Dominikus; Alfian, Achmad; Pratama, Yohanes Dicka (Ann Publisher, 2025)
Industrial waste includes various types of materials that are no longer useful, economically valuable, or desirable in an operational context. Industrial waste management requires a special approach, the potential environmental and health impacts that can be caused. The waste management technology used depends on the type of waste generated, which is already known by the people in Palembang City is a waste management technology that is not so complex in its process. How far the people of Palembang City know the technology and its application needs further research. The purpose of this research is to review the literature and identify waste sources, policies, technologies, inhibiting factors, and assessment of waste management technology. The research method used a case study systematically and holistically to gain a comprehensive understanding with steps; determining research design, case selection, data collection and analysis, preparation of findings, and evaluation, reflection and recommendation of sustainable waste management technology. The results of the study recommend sustainable waste management technology in Palembang City which includes: (a) waste sources come from households, offices, businesses, markets, public facilities and areas, (b) waste management policies are located in Government Regulations: Law, Perpres, Permen and Perda, (c) waste management technology is still not integrated and operates in open dumping, (d) inhibiting factors; institutional aspects, financing, regulations, community participation, technical operations, and (e) the execution of zero waste management and comprehensive waste management technology recommendations that are sustainable and environmentally friendly are highly recommended.